2023
DOI: 10.2337/dc24-s008
|View full text |Cite
|
Sign up to set email alerts
|

8. Obesity and Weight Management for the Prevention and Treatment of Type 2 Diabetes: Standards of Care in Diabetes–2024

Nuha A. ElSayed,
Grazia Aleppo,
Raveendhara R. Bannuru
et al.

Abstract: The American Diabetes Association (ADA) “Standards of Care in Diabetes” includes the ADA’s current clinical practice recommendations and is intended to provide the components of diabetes care, general treatment goals and guidelines, and tools to evaluate quality of care. Members of the ADA Professional Practice Committee, an interprofessional expert committee, are responsible for updating the Standards of Care annually, or more frequently as warranted. For a detailed description of ADA standards, statements, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(12 citation statements)
references
References 141 publications
0
12
0
Order By: Relevance
“…Waist circumference is a better indicator of visceral adiposity than BMI or waist-to-hip ratio and would be relevant in people with a BMI of <30 kg/m 2 to avoid underdiagnosis of excess abdominal fat excess and high cardiometabolic risk [ 19 ]. However, it should be noted that most of the available evidence on the effects of WL strategies is based on percentage of WL [ 20 , 21 ], only BMI is part of the selection criteria for clinical trials [ 22–24 ] and the position statements of the main scientific societies [ 3 , 25 , 26 ] continue to prioritize percentage of WL targets without specific recommendations for changes in body composition. Therefore, despite more advanced techniques to target body fat being an evolving issue, BMI strongly correlates with body fat and associated comorbidities and remains a useful tool for general clinical practice.…”
Section: Abcd T2d Ckd and Cvd: The Adiposity Connectionmentioning
confidence: 99%
See 1 more Smart Citation
“…Waist circumference is a better indicator of visceral adiposity than BMI or waist-to-hip ratio and would be relevant in people with a BMI of <30 kg/m 2 to avoid underdiagnosis of excess abdominal fat excess and high cardiometabolic risk [ 19 ]. However, it should be noted that most of the available evidence on the effects of WL strategies is based on percentage of WL [ 20 , 21 ], only BMI is part of the selection criteria for clinical trials [ 22–24 ] and the position statements of the main scientific societies [ 3 , 25 , 26 ] continue to prioritize percentage of WL targets without specific recommendations for changes in body composition. Therefore, despite more advanced techniques to target body fat being an evolving issue, BMI strongly correlates with body fat and associated comorbidities and remains a useful tool for general clinical practice.…”
Section: Abcd T2d Ckd and Cvd: The Adiposity Connectionmentioning
confidence: 99%
“…The ADA—European Association for the Study of Diabetes (EASD) Standards of Care consider that weight management is an impactful component of glucose-lowering management in T2D [ 26 , 56 ]. A sustained loss of >10% of BW confers disease-modifying effects and the possible remission of T2D, and may also improve long-term CV outcomes and mortality [ 26 ]. In overweight or obese PWT2D, the preferred pharmacotherapy should be a GLP1RA or dual GIP–GLP1RA with greater efficacy in reducing BW (i.e.…”
Section: Therapeutic Translation: Dysfunctional Adipose Tissue Approa...mentioning
confidence: 99%
“…Obesity is a risk factor for T2DM as well as cardiovascular disease, musculoskeletal disease, and many cancers [ 232 ]. Bariatric surgery and weight loss can lead to T2DM remission [ 233 ]. Surgery has been shown to be more effective than medical treatment for long term control of T2DM in obese patients.…”
Section: Type 2 Diabetes Mellitus (T2dm) and Bariatric Surgerymentioning
confidence: 99%
“…The GLP-1 receptor agonist liraglutide at a high dose (administered as a single daily injection of 3 mg subcutaneously) has been approved as an adjunctive medication for weight loss achieved through a low-calorie diet and physical activity in adults with obesity or overweight-related comorbidities, as well as for the treatment of obese children and adolescents aged 12 years or older [ 70 ]. Previous large randomized clinical trials have demonstrated that a 3 mg dose of liraglutide can result in an average weight loss of 5.6 kg over nearly one year in overweight or obese individuals without diabetes [ 71 ].…”
Section: Peptide-based Therapies In the Treatment Of Obesitymentioning
confidence: 99%